Perencanaan Persediaan Bahan Baku Menggunakan Metode Material Requirement Planning (MRP) Produk Minuman Kesehatan Pada UD Pemanah Sakti Abadi Kediri - Muhammad Suryo Budi Harjo (Jurnal Simki Economic, 2019)
This research is motivated by the material procurement planning process that has not used a special method, and the determination of the amount of material needed is only based on the sequence of activities made based on experience. The problems faced by the company can hinder the smooth and timely completion of the resulting product. The purpose of this study is (1) to find out whether the application of the Material Requirement Planning (MRP) method at the UD Pemanah Sakti Abadi company in planning the inventory of raw materials. (2) To determine the determination of the amount of raw material and component inventory in meeting the target. This research technique uses descriptive analysis method with a quantitative approach. The subject of this research is UD Pemanah Sakti Abadi and the object is the supply of flavored syrup products. Data collection techniques were carried out in three ways, namely interviews, observations, and documentation with data analysis techniques using the calculation of the Material Requirement Planning (MRP) analysis method. The conclusion in this study is that the planning for the procurement of flavored syrup products in June 2018 is 5782 bottles. With a product procurement plan of 5782 bottles, the company must provide a total supply of raw materials with components, namely 6,938.4 liters of water, 578.2 kg, 2,891 grams of salt, 5,782 ml of sodium cyclamate, 404.74 grams of sodium benzoate. As for the essence of each flavor, it varies depending on the number of requests for the product. Where Esense for wine is 12.550 ml, wine is 6.155 ml, and Rice Kencur is 10.205 ml. So, after knowing the amount of net requirement for each existing material, for one month the production process is carried out by preparing the needs that are not yet available and working or processing the existing materials into finished goods. That way, there will be no delays in delivery because the production schedule has been arranged correctly.